Rice distribution optimization using initial basic feasible and modified solution to increase food security in West Java - Fachri Al Aziz Putrandi; Divacha Vicha Mollie; Atmadi; Julio Rivaldo Sembiring; Abdul Fakhar (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
Rice is one of the main commodities needed by more than 95% of developing countries, including Indonesia. High population growth that is not accompanied by sufficient rice production will lead to many problems such as malnutrition, famine, and economic crisis, so the availability of rice in Indonesia is the main focus in food security. Farmer welfare is one of the factors in increasing rice production. But in reality, farmers are often constrained by the high cost of distributing rice.  As one of the largest rice producing regions in Indonesia, optimisation of rice distribution costs in West Java needs to be done. the process of optimising rice distribution costs can be done using the transportation method. The transportation method is carried out in 2 stages, namely obtaining the initial solution and the optimal solution. Initial Basic Feasible Solution (IBFS) as one of the approaches in obtaining the initial solution works by considering the average value of new unit costs and columns. As for obtaining the optimal solution, MODI is used, which calculates the opportunity cost of cells that are not given a distribution allocation to assess the optimality of the table. Optimisation of rice distribution using IBFS and MODI resulted in an initial solution of Rp 27,259,921600 and an optimal solution of Rp 27,259,921600 with the Bandung area as the area that supplies the most rice in West Java.